Faktor-Faktor Kesediaan Direlokasi Masyarakat Dari Kawasan Rawan Longsor: Kasus Desa Tengklik, Tawangmangu, Kabupaten Karanganyar - Aryani Aryani; Agung Sugiri (Teknik PWK (Perencanaan Wilayah Kota), 2017)
Tengklik Village is one of the villages on the slopes of Mount Lawu that enter into the area prone to landslides. Current mudslides have caused Tengklik Village to have a high degree of vulnerability to landslides again due to dormant avalanche, where one day if any triggering force will be easy to move again. The mitigation efforts currently being carried out are the relocation of the population within the high land movement area of 37 families. Looking at the relocation process implemented then it can be learned about the factors that lead to successful relocation according to the research approach, then the research question arises: what factors make people willing to be relocated from landslide prone areas of Tengklik Village, Tawangmangu District, Karanganyar Regency? In answering the research questions above, the target to be achieved is to know the factors that make people willing to be relocated from landslide prone areas. This research has 13 factor variables that will be confirmed to the field. The method used in this research is quantitative descriptive method. The result of this research is from 13 factors, there are 11 confirmed factors in the field and 2 unconfirmed factors. Factors that were successfully confirmed were exposure to disasters, access to resources, livelihoods, compensation, new residential locations, the physical condition of new house, the provision of facilities and infrastructure, transparent relocation information, the participation of the community, decisions of fallen people and the existence of attachments between communities. While unconfirmed factors were respondents age and evacuation time